C3 glomerulonephritis associated with monoclonal gammopathy: a retrospective case series study from a single institute in China. Issue 1 (1st January 2021) - Zhang, Xin; Yu, Xiao-Juan; Li, Dan-yang; Wang, Su-xia; Zhou, Fu-de; Zhao, Ming-hui
Abstract: Objective: To investigate the demographic and clinicopathological features and renal outcomes of Chinese patients with C3 glomerulonephritis in the setting of monoclonal gammopathy. Methods: Patients with renal biopsy-proven C3 glomerulonephritis and detectable serum and/or urine monoclonal immunoglobulin from 2006 to 2018 in Peking University First Hospital were included, their clinical data, renal pathology type, treatment, and prognosis were collected and analyzed. Results: Nineteen patients were enrolled, accounting for 24% of C3GN patients in the study period. The mean age of onset was 55 years old and the gender ratio was 4/15 (female/male). The mean eGFR at biopsy was 49.55 ± 29.81 ml/min/1.73m 2 . The prominent clinical manifestations included nephrotic syndrome (58%), anemia (68%), microscopic hematuria and leukocyturia (58%), and hypocomplementemia (13, 68%). The IgG was the most common isotype of monoclonal Ig on immunofixation electrophoresis. Kidney biopsies revealed a relatively prominent MPGN pattern. Only two patients had direct evidence of monocle immunoglobulins acting as C3GN pathogenic factors. Two patients had concurrent TMA-like renal injuries. The median renal survival was 12 and 15 months, respectively in patients receiving conservative therapy and immunosuppressant therapy, without statistical significance. The efficacy of clone-targeted therapy needed further investigation. Plasma exchange therapy only improved one patient's renal outcome. Conclusions: This is the first case series report of C3GN combined with monoclonal Ig in northern China. The renal prognosis of these patients is poor, and immunosuppressant therapies show no advantage over supportive therapy in renal prognosis, while the benefit of clone-targeted chemotherapy is still requiring investigation.